Cellular Automaton Self-Organizing a Mechanical Structure : Behavior of Total System Generated by Local Rules - Inou, Norio; Shimotai, Naoko; Kobayashi, Hiroki (Nihon Kikai Gakkai rombunshuu. A hen, 1995)
This paper describes a cellular automaton generating an adapted structure for an arbitrary loading condition. The mathematical model is based on the remodeling (functional adaptation) of living systems. The model consists of identical cells which mechanically connect with each other. Each cell changes its Young's modulus, sensing the mechanical condition around the cell. We examined the performance of the model, giving each cell local rules with a nonlinear relationship for the change in Young's modulus. The local rules are "death", "birth", and "split" as in living systems. The computer simulation showed that the model formed a clear framed structure satisfying the boundary condition.